PENGARUH MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR TEKNIK DASAR PASSING BAWAH BOLAVOLI DI SMPN 14 PONTIANAK - F38108030, Nikolas Citro Pianus; Supriatna, Eka; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2012)
The effect of cooperative learning model the learning outcomes of the basic techniques of passing the volleyball at the Junior High School 14 pontianak. The problem in this study is